(untitled) (Journal of Hama University, 2021)
This research examines the effect of the US dollar exchange rate against the Syrian pound on the capital structure of non-financial companies listed on the Damascus Stock Exchange, using the method of time-series cross-sectional data (panel data) by applying to a sample consisting of 4 companies (Al-Ahlia Oils Company, Al-Ahlia Transport Company, United Publishing and Advertising Company and the Agricultural Investment Engineering Company - Nama), and during the time period from 2009 to 2018, the research reached a set of conclusions, the most important of which is the influence of the capital structure of the companies studied by the consequences of economic conditions, which led to a decrease in the ratios of the capital structure during the studied period In addition to the presence of a negative and statistically significant effect of the exchange rate on the capital structure of the companies studied